Mindful walking as a mindfulness technique and prosocial behavior of students at ekayana ehipassiko school - Wina Wina; Hendri Ardianto; Ayu Andriyaningsih (Universitas Sebelas Maret, 2025)
This study aims to examine in depth the effect of mindful walking practices on the development of prosocial behavior among students at Ekayana Ehipassiko School. Prosocial behavior, which includes empathy, willingness to help, cooperation, and participation in social activities, is a crucial aspect in shaping students' character. The focus of this study is motivated by several problems identified in the school environment, including the tendency of students to be reluctant to help friends who are experiencing academic difficulties, a lack of empathy for the emotional problems of others, a preference for working independently rather than collaborating in groups, and low participation in social activities such as community service and mutual cooperation. In addition, the learning methods that have been applied so far are considered not optimal in fostering prosocial attitudes in students. This study uses a descriptive quantitative approach with a survey method. The research sample consisted of 91 students distributed across three grade levels, namely 32 seventh-grade students, 35 eighth-grade students, and 24 ninth-grade students. Data collection was conducted during the 2024/2025 academic year using research instruments designed to measure the level of mindfulness after practicing mindful walking and students' prosocial behavior tendencies. The results of the statistical analysis showed significant findings. The t-value of 11.597 with a significance level of 0.000 (p < 0.05) indicates a strong influence between mindful walking and an increase in prosocial behavior. Furthermore, the coefficient of determination (R²) of 0.602 reveals that 60.2% of the variation in students' prosocial behavior can be explained by the practice of mindful walking, while the remaining 39.8% is influenced by external factors such as family environment, parenting patterns, or peer influence. These findings strengthen the empirical evidence that mindfulness-based interventions such as mindful walking can be an effective strategy in fostering prosocial attitudes among students.